Collier's conflict of laws - Rogerson, Pippa (Cambridge, 2013)
"This reworked version of Conflict of Laws introduces a new generation of students to the classic. It has been completely rewritten to reflect all the recent developments including the increased legislation and case law in the field. The author's teaching experience is reflected in her ability to provide students with a clear statement of rules which sets out a framework to the subject, before adding detail and critical analysis. Recognising that the procedural aspect of the subject challenges most students, the book explores conflict of laws in its practical context to ensure understanding. Teachers will appreciate the logical structure, which has been reworked to reflect teaching in the field today. Retaining the authority that was the hallmark of the previous edition, this contemporary and comprehensive textbook is essential reading"--